Caracterización epidemiológica de los casos fatales con reporte positivo para Tramadol atendidos por el instituto nacional de medicina legal y ciencias forenses, sede Bogotá, entre 2013 Y 2018 (2020)
Tramadol is an analgesic family of opioids, which has monoaminergic effects on its mechanism of action. In Colombia this is regulated with medical establishing sale with medical prescription; although this has been reported consumption purposes including recreation, as I express the United Nations Office on Drugs and Crime, in its World Report 2018 in Africa. For this reason we sought to characterize epidemiologically fatal cases with positive report for tramadol attended by the National Institute of Legal Medicine and Forensic Sciences, Bogotá, between 2013 and 2018, through a cross-sectional study. Thus a total of 35 cases, of which most are occupationally active adults and male was obtained. In fact, 40,00% had cause of death tramadol intoxication, in any of its various presentations. Added to this, 25,71% of the samples showed any laboratory other substance present. By contrast, the existence of the above 3 cases of minors who had an accidental with consumption due to mistakes in handling the drug is observed.